The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.15690/vramn1426
|View full text |Cite
|
Sign up to set email alerts
|

Problems of Psycho-Emotional Well-Being of Medical Personnel Working in the Context of the COVID-19 Pandemic

Abstract: Background. The COVID-19 pandemic has a significant impact on the mental state of not only quarantined citizens and patients, but also health workers. Aims asessment of the mental health of doctors involved in work in the red zone during the COVID-19 pandemic. Materials and methods. 77 respondents were interviewed using the HADS questionnaires and the Maslach burnout test. For statistical data processing Microsoft Office Excel 2016, IBM SPSS were used. Results. An increase on the depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Based on these studies, coping strategies were suggested. For instance, social support can improve the mental health of medical staff, who treat patients with COVID-19, and reduce the risk of sleep disorders, associated economic losses, unintentional medical errors and reduced working efficiency [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these studies, coping strategies were suggested. For instance, social support can improve the mental health of medical staff, who treat patients with COVID-19, and reduce the risk of sleep disorders, associated economic losses, unintentional medical errors and reduced working efficiency [27][28][29].…”
Section: Introductionmentioning
confidence: 99%